2014
DOI: 10.1647/2012-036r.1
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Sheath Tumor in a Subadult Golden Eagle (Aquila chrysaetos)

Abstract: A 5-year-old, female golden eagle (Aquila chrysaetos) was admitted with tetraplegia that progressed to a nonambulatory, spastic tetraparesis after a few days of treatment. Clinical and radiologic examinations, including radiography, computed tomography scan, and myelography, were indicative of neoplasia involving a spinal nerve root. Postmortem magnetic resonance imaging and necropsy findings confirmed the diagnosis of a peripheral nerve sheath neoplasia, not, to our knowledge, previously reported in a raptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Magnetic resonance imaging has been proven to be useful to assess chronic sinonasal diseases in psittacine birds, diagnose hydrocephalus in African grey parrots, and has been shown to be superior to radiography in evaluating spinal cord trauma in three bald eagles . Magnetic resonance imaging has been used to diagnose a peripheral nerve sheath tumor in a subadult eagle and peripheral vestibular disease in a Chinese goose . Recently, a pilot study has demonstrated the usefulness of MRI in the detection of brain lesions caused by severe lead poisoning in bald eagles .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging has been proven to be useful to assess chronic sinonasal diseases in psittacine birds, diagnose hydrocephalus in African grey parrots, and has been shown to be superior to radiography in evaluating spinal cord trauma in three bald eagles . Magnetic resonance imaging has been used to diagnose a peripheral nerve sheath tumor in a subadult eagle and peripheral vestibular disease in a Chinese goose . Recently, a pilot study has demonstrated the usefulness of MRI in the detection of brain lesions caused by severe lead poisoning in bald eagles .…”
Section: Introductionmentioning
confidence: 99%
“…55 The toucan presented with a soft tissue mass adhered to the pectoral musculature, 55 while the eagle presented with tetraplegia due to the tumor impinging on a spinal nerve root. 54 The lovebird with the peripheral nerve sheath tumor in our study presented with a soft tissue mass on one wing and associated wing droop, but the bird remained in good body condition.…”
Section: Discussionmentioning
confidence: 67%
“…The incidence of mesenchymal tissue neoplasms is variable with species, but they are reportedly the second most common type of neoplasm in cats and the third most frequently identified tumor in dogs. 52 In birds, there are numerous reports of these tumors affecting the integument, 2,53 connective tissues, 54,55 reproductive tract, 2,3,6,7,46 cardiorespiratory system, 3,46,[56][57][58] gastrointestinal tract, 7,59 kidney, 60 and musculoskeletal system. 2,[61][62][63][64] In this study, the reproductive tract and the integument were the most frequently identified anatomical locations of mesenchymal cell tumors in budgerigars.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications of CT and MRI anatomy in avian species exist. However, those are mainly focused on sinonasal cavities, eyes, head/brain, respiratory tract or spine (de Francisco et al, 2016; Delk et al, 2014; Fleming et al, 2003; Gumpenberger & Henninger, 2001; Gumpenberger & Kolm, 2006; Jones et al, 2019; Krautwald‐Junghanns et al, 1998; Krautwald‐Junghanns et al, 1993; Petnehazy et al, 2012; Pye et al, 2000; Romagnano et al, 1996; Schwarz et al, 2016; Stauber et al, 2007; Verhoye et al, 1998; Wernick et al, 2014) and rarely in the coelomic cavity (Orosz & Toal, 1992; Petnehazy et al, 2012; Romagnano et al, 1996). In the present study, the CT and MRI anatomy of the coelomic cavity in Pekin ducks was provided and corresponding frozen cadaver section photos were provided for CT images.…”
Section: Discussionmentioning
confidence: 99%